Nitrile Hydration Reaction Using Copper Iodide/Cesium Carbonate/DBU in Nitromethane–Water - Kuwabara, Jun; Sawada, Yoshiharu; Yoshimatsu, Mitsuhiro (Synlett, 2018)
The catalytic nitrile hydration (amide formation) in a copper iodide/cesium carbonate/1,8-diazabicyclo[5.4.0]undec-7-ene/nitromethane–water system is described. The protocol is robust and reliable; it can be applied to a broad range of substrates with high chemoselectivity.
Keywords: catalysis; copper iodide; nitrile hydration; nitromethane–water; primary amides